EKSPLORASI BENTUK WAYANG KAYON DALAM PERANCANGAN DESAIN RAK MODULAR BERBAHAN ROTAN - Kurniawan, Mohd Ridho; Maudi, Yulia Yasmin (INSIDE : Jurnal Desain Interior, 2025)
This study aims to explore the visual form and philosophical value of wayang kayon as an inspiration in designing modular shelves made of rattan. Wayang kayon, as a cosmological symbol in wayang performances, represents the balance, transition, and harmony of the universe. The design approach is carried out exploratively by adapting the silhouette and ornaments of kayon into a functional and aesthetic modular system. Rattan was chosen as the main material because of its flexible, lightweight, and environmentally friendly properties, as well as supporting the formation of organic structures. The research methods include literature studies, exploration of forms, and development of design prototypes. The results show that the integration of the form of kayon and the characteristics of rattan produces a modular shelf design that is not only spatially adaptive, but also contains strong local cultural values. This study contributes to the development of interior design based on local wisdom.